Neuroprotective effects of total saponins from Rubus parvifolius L. on cerebral ischemia/ reperfusion injury in rats - Wang, Jisheng; Zhang, Fang; Tang, Li; Sun, Liqiong; Song, Xiaolin; Cao, Lisha; Qiu, Zongyin; Zhou, Chenglin (Neural regeneration research, 2012)
This study examines the neuroprotective effects and mechanisms of action of total saponins from Rubus parvifolius L. （TSRP） on focal cerebral ischemia and reperfusion injury in rats. Focal cerebral ischemia and reperfusion injury was performed in rats using the suture method. The results indicate that intragastric injection of TSRP, at 5, 10 and 20 mg/kg, could decrease neurological impairment, reduce cerebral infarct volume, diminish pathological changes, and significantly inhibit the apoptosis of neurons surrounding the ischemic area. In addition, TSRP upregulated the expression of the anti-apoptotic factor Bcl-2, at the protein and mRNA levels, and it downregulated the expression of the pro-apoptotic factor Bax, at the protein and mRNA levels. These findings indicate that TSRP protects against cerebral ischemia/reperfusion injury, and that it may do so by regulating the expression of Bcl-2 and Bax.